The Concept of Post-humanism and Its Reflections on Tourism Education - Genç, Ruhet (The Gaze: Journal of Tourism and Hospitality, 2019)
The aim of this manuscript is to investigate the influence the impacts of post-humanism on tourism education. The paper will start with a body of literature on post-humanism based on the previous studies and debates in the academia. The methodology will be literature review and critical evaluation of the findings. As a conclusion, the study suggests that the Post-humanist reflection in tourism education will contribute positively to the tourism sector, specifically regarding to sustainability issues. The manuscript will also suggest a model in order to provide a quantitative analysis for the post-humanism, including the technological advancements and environmental regeneration variables, along with possible economic and social impacts. In short, establishment of a tourism education that considerably pays attention to the benefits of post-humanism will be essential for functionality and effectiveness of tourism practice in the future.